Coupling Interaction of Surrounding Soil-Buried Pipeline and Additional Stress in Subsidence Soil. (25th August 2021) - Ding, Yahong; Yang, Heng; Xu, Ping; Zhang, Minxia; Hou, Zhenguo
Abstract : In the process of underground resource exploitation, the induced surface subsidence easily leads to the deformation and failure of buried pipeline. And in the process of soil subsidence, the complex interaction between buried pipeline and surrounding soil occurs, which leads to deformation and additional stress in buried pipeline. In this paper, a laboratory test system is designed and developed to analyze the influence of buried depth, cohesion of soil, and angle of internal friction on stress, in order to obtain the deformation mechanism of pipe-soil and the pressure around the pipe and the distribution of additional axial stress along the pipeline. The research results show that in the process of subsidence, the synergistic deformation between the pipe and soil at both ends of the subsidence area is maintained, while there is a compressive nonsynergistic deformation zone in the soil at the top of the pipe, and the deformation zone in the cohesion-less soil and the cohesive soil presents a spire shape and an arch shape, respectively. Areas of maximum additional tensile and compressive stresses occur in the area of maximum curvature and the central position. In addition, the smaller the burial depth, the earlier the unloading phenomenon occurs; and the additional stress in buried pipe in cohesion-less soil is significantly less than that in cohesive soil, and the unloading phenomenon occurs earlier. The research results provide the basis for disaster prevention of buried petroleum transmission pipeline in subsidence process.